DESAIN NORMATIF TENTANG KEBIJAKAN FISKAL PADA MASA DINASTI ABBASIYAH: STUDI ATAS PEMIKIRAN AL-MAWARDI DALAM KITAB AL-AHKAM AL-SULTHANIYAH - Rini Utari utari; Muhammad Maulana (LPPM STAI Muhammadiyah Probolinggo, 2026)
This article aims to analyze fiscal policy from Al-Mawardi's perspective in the book Al-Ahkam Al-Sulthaniyah. Using a library research method and qualitative analysis, this study demonstrates that Al-Mawardi's ideas do not merely classify authority income posts such as zakat (alms), kharaj (land tax), jizyah (poll tax), ghanimah (spoils of war), or temporary tax instruments (dharibah). Beyond that, he emphasizes the principles of balance, propriety, and public welfare as the foundation of public cash management. These findings indicate that the moral dimension in Al-Mawardi's thesis is highly contextual for implementation into today's modern financial structures, particularly regarding budget information transparency, strengthening safety nets for marginalized groups, and responsibility in managing community funds. In his thought, state revenue sources include zakat, kharaj, jizyah, fai’ (spoils acquired without fighting), and ghanimah, which are managed through the baitul mal institution. In its distribution, the state bears the responsibility to meet public needs, maintain security, finance government administration, and assist vulnerable groups. The fiscal concept offered by Al-Mawardi emphasizes not only administrative aspects but also the moral and ethical dimensions of governance.